Device‐associated thrombus formation after left atrial appendage occlusion: A systematic review of events reported with the Watchman, the Amplatzer Cardiac Plug and the Amulet. Issue 5 (1st February 2017) - Lempereur, Mathieu; Aminian, Adel; Freixa, Xavier; Gafoor, Sameer; Kefer, Joelle; Tzikas, Apostolos; Legrand, Victor; Saw, Jacqueline
Abstract : Objectives: This study aimed to provide a systematic review of device‐associated thrombosis (DAT) after left atrial appendage occlusion (LAAO) with the Watchman, Amplatzer Cardiac Plug, and Amulet devices. Background: DAT is known as a complication of LAAO but data about its clinical impact is scarce. Methods: A systematic review of studies evaluating the incidence, treatment and clinical implications of DAT from January 2008 to September 2015 was conducted. Results: A total of 30 studies describing DAT events were included in the analysis. The overall incidence of DAT was 3.9% (82 DAT for 2118 implanted devices). The median time from procedure to diagnosis of DAT was 1.5 months (IQR: 0–2.9). Most cases were diagnosed with transesophageal echocardiogram (TEE). The treatment consisted of low molecular weight heparin (LMWH) in 45.5% of cases, and oral anticoagulation (OAC) or other treatment modalities in 54.5%. Complete thrombus resolution was achieved in 95.0% of cases (100% with LMWH and 89.5% with OAC). Treatment duration varied greatly with a median treatment duration of 45 days (IQR: 14–135). Clinical events related to DAT consisted of neurologic events namely two transient ischemic attacks (2.4%) and four ischemic strokes (4.9%). Conclusions: DAT is an infrequent complication of percutaneous LAAO. It occurs mainly early after the procedure and is associated with a low rate of neurological complications. In the majority of cases, diagnosis is made during follow‐up imaging with TEE. Anticoagulation treatment seems to be safe and highly effective. Further studies are needed to evaluate the optimal management of DAT. © 2017 Wiley Periodicals, Inc.